O papel do docente na apropriação e oportunização da paisagem urbana como espaço fruitivo criador: The teacher’s role in the appropriation and opportunity of the urban landscape as a creative fruitive space - Comério, Eloíza; Jeronymo, Ciliani Celante Eloi (Revista do Colóquio, 2023)
concept of landscape and Urban Art. It enhances the teaching role to awaken the feeling of belonging in basic education students from the contact with the public space that surrounds them. It gives students the opportunity to experience heritage education content, through the affective path recorded from interactive activities. The object of this educational action allowed for ’social’, ’educational’ and ’cultural’ dialogue, through teaching intervention, which aims to strengthen the process of creative fruition in the school space from the exploration and knowledge of the urban landscape and its monuments. This educational action in Basic Education allowed the ’literacy of the look’, the construction of an affective path and favored the appropriation and proliferation of Heritage Education in the School Curriculum, through intervention activities in methodological practice, and in the teaching role in teaching of art